1996
DOI: 10.1046/j.1468-2982.1996.1606423.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Serotonin in Patients with Analgesic-Induced Headache

Abstract: The purpose of this study was to investigate the role of serotonin (5HT) in patients with analgesic-induced headache (AIH). We estimated platelet 5HT concentration in patients with AIH, migraine patients and non-headache controls, by using high performance liquid chromatography with electrochemical detection. Our results revealed a significant decrease (p < 0.001) in platelet 5HT content in patients with AIH as compared to migraine patients and non-headache controls (221.8 +/- 30.7, 445.3 +/- 37.4 and 467.2 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 12 publications
5
51
2
Order By: Relevance
“…Tryptophan depletion increases nausea, headache, and photophobia in migraineurs [20]. Decreases in 5-HT levels also were reported in patients with MOH [21]. Animal experiments show that dysfunction of this transmitter system leads to several changes in the cerebral cortex and trigeminal system, which can increase the susceptibility of headache attacks.…”
Section: Medication-overuse Headache and Alteration Of Central Modulamentioning
confidence: 92%
“…Tryptophan depletion increases nausea, headache, and photophobia in migraineurs [20]. Decreases in 5-HT levels also were reported in patients with MOH [21]. Animal experiments show that dysfunction of this transmitter system leads to several changes in the cerebral cortex and trigeminal system, which can increase the susceptibility of headache attacks.…”
Section: Medication-overuse Headache and Alteration Of Central Modulamentioning
confidence: 92%
“…A derangement of the central serotonin-dependent endogenous pain control system induced by chronic medication has been proposed [16]. Observation of a decrease in serotonin in patients with MOH supports this hypothesis [23].…”
Section: Discussionmentioning
confidence: 97%
“…This activity may particularly be enhanced during druginduced headache, a mechanism similar to that occurring during opioid withdrawal. A decrease in platelet serotonin in migraine patients overusing analgesics has been demonstrated; this allows us to hypothesize that analgesic overuse depletes serotonin from storage sites, leading to an increase in the frequency of attacks [40,44].…”
Section: Cdh and Drug Abusementioning
confidence: 94%
“…A more recent study carried out by Srikiatkhachorn and Anthony [43] demonstrated a reduced content and uptake of 5-HT, as well as the upregulation of 5HT 2 receptors in platelets of patients with analgesic-induced headache. According to the authors, these findings suggested that analgesic-induced suppression of 5-HT uptake interferes with the function of the pain modulatory system in the brainstem [44].…”
Section: Serotoninergic Pathways In Cdh and Their Relation To Nitric mentioning
confidence: 99%